Approach to Negotiation Accounting as a Mechanism to Enhance Tax awareness (Comprehensive Journal of Science, 2026)
The main objective of conducting this study is to know the role of the negotiated accounting approach in improving tax awareness among taxpayers and reducing tax disputes. To achieve this objective, a questionnaire containing 25 questions was used and distributed to 80 employees who work within the General Tax Authority in Libya, the first hypothesis of this study was: There is a statistically significant relationship between the negotiated accounting approach and improving tax awareness, and the second hypothesis, there is a statistically significant relationship between the negotiated accounting approach and reducing tax disputes, which was proven through the use of the Statistical Package for the Social Sciences (SPSS). The study recommended the necessity of direct negotiation between the General Tax Authority and taxpayers in all matters related to the tax process in order to improve tax awareness among taxpayers and reduce tax disputes.As for future recommendations for researchers, a study can be conducted on the role of the negotiation accounting approach in improving tax performance, and the impact of negotiation accounting in increasing tax revenues.
Keywords: negotiated accounting approach, tax awareness, tax obligations